Respuesta :

Answer:

[tex]a = \dfrac{46}{17}[/tex]

[tex] b = 0 [/tex]

Step-by-step explanation:

[tex] \dfrac{2\sqrt{5} + \sqrt{3}}{2\sqrt{5} - \sqrt{3}} + \dfrac{2\sqrt{5} - \sqrt{3}}{2\sqrt{5} + \sqrt{3}} = [/tex]

[tex] = \dfrac{2\sqrt{5} + \sqrt{3}}{2\sqrt{5} - \sqrt{3}} \times \dfrac{2\sqrt{5} + \sqrt{3}}{2\sqrt{5} + \sqrt{3}} + \dfrac{2\sqrt{5} - \sqrt{3}}{2\sqrt{5} + \sqrt{3}} \times \dfrac{2\sqrt{5} - \sqrt{3}}{2\sqrt{5} - \sqrt{3}} [/tex]

[tex] = \dfrac{23 + 4\sqrt{15}}{17} + \dfrac{23 - 4\sqrt{15}}{17} [/tex]

[tex] = \dfrac{46}{17} [/tex]

[tex]a = \dfrac{46}{17}[/tex]

[tex] b = 0 [/tex]